ANALISIS EFEKTIVITAS PENGGUNAAN MODA TRANSPORTASI BERBASIS ONLINE - Amril Makruf (Universitas Sang Bumi Ruwa Jurai, 2018)
Online transportation is generally a private vehicle either a four-wheeled or two- wheeled vehicle which is operationalized as a mode of transportation that orders are made with an online application and aims to facilitate user access. Online transportation has many advantages such as easier booking through the application, relatively lower fares, short travel time and going directly to the destination location. The emergence of online transportation also has a variety of negative impacts, one of which is the unrest between online transportation so that people have the choice of which mode is most appropriate to support their activities. The results of calculations with the SPSS application obtained sig value kurang dari 0.05 and calculated F value of 168.972 greater than 1.97 F table. Based on the results of these calculations it can be concluded that the component factor selection mode significantly influences the mode of online transportation used so that the model can be used simultaneously. Based on the results of the regression test, the calculated T value lebih dari T table is 8.823 lebih dari 0.519 and the value of sig (0.00) kurang dari 0.05, which means that the independent variable (X) affects the dependent variable (Y). This proves that the component mode selection factor influences the mode of transportation chosen by the user. The choice of modes of online transportation both Go-jek and Grab is a benchmark for users of modes to determine the chosen mode to the airport.